Best Answer

3xx-588

3(xx-196)

Factor (long):

xx+0x-196

axx+bx+c

a=1

b=0

c=-196

Multiply a and c:

1*-196=-196

Find multiples of ac that add up to b (d,e [ie de=ac, d+e=b]):

-196=-1*2*2*7*7,

-2*98, 2*-98

-7*28, 7*-28

-4*49, 4*-49

-14*14,

Rewrite axx+bx+c into axx+dx+ex+c:

3(xx-14x+14x-196)

Factor sets of terms (ie axx+dx, and ex+c):

3(xx-14x+14x-196)

3(x(x-14)+14(x-14))

Combine like terms:

3(x(x-14)+14(x-14))

3(x-14)(x+14)

Factor (short):

3(xx+0x-196)

Factors of -196, find which ones add up to 0

-196=-1*2*2*7*7,

-2*98, 2*-98

-7*28, 7*-28

-4*49, 4*-49

-14*14,

Rewrite in form of (x+d)(x+e)

3(x+14)(x-14)

Factor (shorter):

-when a polynomial takes the form of xx-c, it can be factored into the form:

(x+sqrt(c))(x-sqrt(c))

sqrt(196)=14,-14

3(x+14)(x-14)

Study guides

☆☆

More answers

That doesn't factor neatly. Applying the quadratic formula, we find two real solutions: (0 plus or minus the square root of 30) divided by 3.

x = 1.8257418583505538

x = -1.8257418583505538

3x2 - 3x - 6 = 3(x2 - x - 2) = 3 (x + 1) (x - 2)

Since 3 squared is 9 and 9 - 9 equals 0, that's going to be tough to factor.

3x2 - 9 factors to 3(x2 - 3)

(3x - 1)(x + 2)

3(x - 7)(x + 7)

Q: How do you factor 3x squared minus 3x minus 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Movies & Television

2(5r + 6)(5r - 6)

(2x - 3)(3x + 2)

6(ab - ac + b2 - bc)

3X2 - 123(X2 - 4)=========All the factoring that can be done here.

if by that you mean 3x - 125 well you can't. unless you want to get a fraction or a decimal which is not the whole point of factorizing you could facorising 3x -18 by dividing each of the number by 3 eg. 3x-18 =3(x-6)

Related questions

(x + 3)(3x - 2)

(x - 6)(x + 9)

Yes, but not in rational terms. The factorisation is: {x - [3-sqrt(57)]/6} * {x - [3+sqrt(57)]/6}

3x2 -14x -24 can be factored as (3x + 4)(x - 6).

That factors to (x - 3)(x + 6)

(x - 2)(2x + 3)

Your factors must begin 3x and x to give 3x2. The factors of 12 are 1/12, 2/6 and 3/4. Which pair, together with 3x and x, can add to -5? 3 and 4 seem to fit the bill: (3x + 4)(x - 3)

(5x - 6)(5x + 6)

(x + 6)(x - 6)

2(5r + 6)(5r - 6)

x squared minus 12 x plus 36 = (x - 6)(x - 6)

y² - y - 6 = (y + 2)(y - 3)